Assessment of cardiac and vessel functions in childhood psoriasis - ŞAYLAN ÇEVİK, BERNA; AKALIN, FİGEN; ERGUN, SAFİYE ATLAS TÜLİN (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2019)
Background/aim: Psoriasis is a chronic inflammatory disease. The effect of psoriasis on the cardiovascular system has not been studied in children before. We studied ventricular strain and vascular functions to assess early cardiovascular effects of psoriasis during childhood. Materials and methods: The study population consisted of 20 psoriatic and 20 age- and sex-matched control subjects. Two-dimensional echocardiography images, longitudinal and global strain, and carotid and brachial ultrasound studies were performed. Results: The mean age of psoriatic children was 14 +/- 0.89 years and that of the controls was 14.05 +/- 0.88. There were significant increases in terms of interventricular septum diastolic and left ventricular posterior wall diastolic diameter and decreases in mitral E, mitral A, and E/A values between groups. Tissue Doppler imaging revealed significant differences between groups in terms of lateral annulus E', A', E'/A, isovolumetric contraction time, and ejection time. Aortic stiffness was significantly higher and global circumferential strain and longitudinal strain were significantly lower in the psoriasis group. Carotid intima media thickness and flow-mediated dilatation did not differ significantly between the groups. Conclusion: Cardiac left ventricular and arterial functions are affected in psoriatic children and may be an alarming sign of atherosclerotic heart disease in the long term. Early detection of these changes may be helpful for eliminating other risk factors.
Keywords: Psoriasis; childhood; echocardiography; ventricular strain; arterial elasticity; CARDIOVASCULAR-DISEASE; PLAQUE PSORIASIS; ATHEROSCLEROSIS; PATHOGENESIS; DYSFUNCTION; SEVERITY; STRAIN